“Smoking your child’s job away”: Parental smoking during one’s childhood and the probability of being employed in adulthood - Prakash, Kushneel; Kumar, Sanjesh (My University, 2021)
We examine the relationship between parental smoking in childhood and the probability of being employed in adulthood. To do so, we use 18 waves of the nationally representative longitudinal data from the Household, Income, and Labour Dynamics in Australia (HILDA) survey. We find that parental smoking in childhood is an important factor contributing to the likelihood of individuals being unemployed in adulthood. Our estimate suggests that individuals whose parents smoked during their childhood have 1.7 percentage points lower probability of being employed in adulthood than individuals of non-smoking parents. This finding is robust to the use of bounding approach to test for coefficient stability and matching methods to attribute causal interpretation. We find that self-health and mental health, along with non-cognitive skills in the form of emotional stability and conscientiousness in adulthood are important channels through which exposure to parental smoking in childhood influences the probability of employment in adulthood.
Melbourne Institute Working Paper Series
Keywords: Childhood and child development; Health and wellbeing; Labour market